Analisis Kombinasi Kerugian dan Keuntungan Pedagang Kaki Lima Gerbang I Unimed Ketika Penggusuran - Andini Ginting; Irene Yoseva; Muhammad Akbar; Reina Mawar; Ruth Miranda (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to analyze the combination of losses and benefits experienced by street vendors at Gate 1 of the State University of Medan (UNIMED) in the context of eviction. The research method used is a qualitative approach with data collection through in-depth interviews and observation of street vendors operating in the Gate 1 area of UNIMED. The research findings indicate that street vendors experience losses in the form of loss of vending space, loss of loyal customers, financial losses, as well as decreased income and well-being as a result of the eviction carried out by the university. However, there are also benefits such as understanding and experience in facing changes in the business environment, support from the community, as well as new opportunities in seeking alternative locations or diversifying businesses. Street vendors at Gate 1 of UNIMED face a complex combination of losses and benefits in dealing with eviction. They have to face challenges in maintaining their business sustainability, coping with significant losses, as well as dealing with uncertainty and changes in business patterns.